Reduced apoptosis in Chinese hamster ovary cells via optimized CRISPR interference - Xiong, Kai; Marquart, Kim Fabiano; la Cour Karottki, Karen Julie; Li, Shangzhong; Shamie, Isaac; Lee, Jae Seong; Gerling, Signe; Yeo, Nan Cher; Chavez, Alejandro; Lee, Gyun Min; Lewis, Nathan E.; Kildegaard, Helene Faustrup (Biotechnology and Bioengineering, 2019)
Chinese hamster ovary (CHO) cells are widely used for biopharmaceutical protein production. One challenge limiting CHO cell productivity is apoptosis stemming from cellular stress during protein production. Here we applied CRISPR interference (CRISPRi) to downregulate the endogenous expression of apoptotic genes Bak, Bax, and Casp3 in CHO cells. In addition to reduced apoptosis, mitochondrial membrane integrity was improved and the caspase activity was reduced. Moreover, we optimized the CRISPRi system to enhance the gene repression efficiency in CHO cells by testing different repressor fusion types. An improved Cas9 repressor has been identified by applying C-terminal fusion of a bipartite repressor domain, KRAB–MeCP2, to nuclease-deficient Cas9. These results collectively demonstrate that CHO cells can be rescued from cell apoptosis by targeted gene repression using the CRISPRi system.
Keywords: Biopharmaceutical proteins; Casp3; Caspases; Chinese Hamster ovary cells; CRISPRi; Endogenous expression; Mitochondrial membranes; Protein production; Animals; Apoptosis; bcl-2 Homologous Antagonist-Killer Protein; bcl-2-Associated X Protein; Caspase 3; CHO Cells; Cricetulus; CRISPR-Associated Protein 9; CRISPR-Cas Systems; Gene Targeting; apoptosis; Bak; Bax; Casp3; caspase; CHO; CRISPRi; mitochondrial membrane integrity